A randomized controlled trial of vocational intervention for young people with first‐episode psychosis: method. Issue 3 (14th July 2013) - Killackey, Eóin; Allott, Kelly; Cotton, Susan M.; Jackson, Henry; Scutella, Rosanna; Tseng, Yi‐Ping; Borland, Jeff; Proffitt, Tina‐Marie; Hunt, Sally; Kay‐Lambkin, Frances; Chinnery, Gina; Baksheev, Gennady; et al.
Abstract: Aim: Young people who are experiencing first‐episode psychosis (FEP) are at increased risk of being unemployed compared to either their same age peers in the general population, or those with other mental illnesses. Significant research has been conducted examining employment interventions for those with chronic psychotic illness. This has yielded strong results in favour of an intervention called individual placement and support (IPS). However, significantly less work has examined the benefit of this approach to those in FEP when the potential for vocational rehabilitation is perhaps greater. This study adds to the knowledge of vocational intervention in first‐episode psychotic illness. Additionally, it expands this work into the areas of cognition, social cognition, social inclusion and economics. Methods: The study is a single‐blind, randomized controlled trial comparing receiving high‐quality FEP treatment as usual plus IPS (IPS + TAU) to a FEP treatment as usual (TAU) intervention alone within a specialized FEP service. Results: The study recruited 146 people attending a first‐episode psychosis service over 2 years. They were assessed at baseline, 6 months (end of intervention) 12 and 18 months with a battery covering psychopathology, economic, demographic, social cognitive, cognitive and diagnostic variables. Conclusions: This paper describes the methodology for the largest attempted study of IPS in FEP. This study has the capacity to answer questions about the benefits on illness and economic impacts of vocational recovery in FEP. Further, it has the capacity to extend knowledge about the contribution of cognitive and social cognitive factors to recovery in this domain.